Estimating the impact of gst on cost of production and cost of living in Malaysia - Hassan, A. A. G. (Penerbit Universiti Kebangsaan Malaysia, 2016)
The implementation of Goods and Services Tax (GST) is often attributed as the main cause of the rising prices of goods and services. The main objective of this study is to estimate the extent of GST implementation impact on the costs of production, which in turn have implication on households' living costs. To achieve these objectives, the input-output price model is developed with modifications to take into account three different tax categories namely standard-rated supplies, zero-rated supplies and exempt supplies. The study finds that the implementation of the GST tends to benefit the economy. GST has the potential to reduce the prices of goods and services by 7.4% compared to only 2.0% expected price increase. The impact of this 5.4% price reduction not only increases the purchasing power of household but also has the potential to narrow the consumption gap between ethnic groups and income classes. However, the actual benefits to the economy depending on the compliance rates of industries to the GST system.